Daily field checking list by Walter Rosene, March 10, 1940 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Robert Walker, March 10, 1940. Also notes a Great Horned Owl's nest with two young. Plustek--flatbed